Graduate students’ civic orientation: applying and testing an instrument - Snejana Slantcheva-Durst (Discover Education)
Abstract This study assesses the civic orientation of graduate students via the “Importance of Social Action Engagement” scale and tests that instrument’s construct validity and reliability when applied to graduate students. The study contributes to our understanding of the levels of graduate students’ willingness to engage with social issues, and to our ability to gauge those levels. The study’s results, based on a sample of 367 survey responses, reports on moderate levels of civic orientation amongst graduate students, and provides evidence of the construct validity and reliability of the instrument items when used with graduate students, and the overall instruments’ effectiveness in the initial exploration of graduate students’ orientation towards social engagement. The results offer useful feedback to graduate student program directors and faculty on the need to incorporate learning initiatives that actively engage their students with social issues, and suggest a viable tool to measure students’ civic orientation.